Extracorporeal membrane oxygenation for severe acute respiratory distress syndrome in children with leukemia/lymphoma: A retrospective case series - Zhang, Yucai; Zhou, Yiping; Shi, Jingyi; Shan, Yijun; Sun, Ting; Wang, Chunxia; Shao, Jingbo; Cui, Yun (Frontiers in Pediatrics, 2022)
Objective: The cancer patients with severe acute respiratory distress syndrome (ARDS) benefit from extracorporeal membrane oxygenation (ECMO) remains unanswered. We analyzed clinical characteristics and outcomes of pediatric leukemia / lymphomas patients who developed ARDS treated with ECMO. Methods: Pediatric leukemia or lymphomas patients with ARDS underwent ECMO between August 2017 and December 2021 were retrospectively analyzed in a tertiary pediatric intensive care unit (PICU). Results: Seven patients with median age 53(IQR 42 to 117) months and 4 males were included. Six cases of leukemia (5 of acute lymphocytic leukemia [ALL]and 1 of acute myelogenous leukemia [AML, M5]) and 1 of non-Hodgkin lymphoma with severe ARDS received ECMO on chemotherapy period. The etiology of ARDS is community or chemotherapy-associated bacterial or/and fungal or viral infection. All patients received chemotherapy in the two weeks prior to ECMO and five were neutropenic at initial ECMO. Six cases underwent veno-arterial ECMO and 1 for veno-venous ECMO. The median duration of ECMO support was 122(IQR 56 to 166) hours. Overall, 42.9% (three of seven) survived to hospital discharge and 28.6% (two of seven) six months survival rate. Bleeding was the mainly ECMO-associated complications occurring in 7 patients, and following by nosocomial infection in 4 cases. All patients required vasopressor support and 6 received continuous renal replacement therapy. Conclusion: Our experiences suggest that rescue ECMO provides a selective treatment strategy in childhood hematologic malignancies with severe ARDS.